Post-transcriptional regulation of gene expression in bacterial pathogens by toxin-antitoxin systems - Bertram, Ralph; Schuster, Christopher F. (Frontiers in Cellular and Infection Microbiology, 2014)
Toxin-antitoxin (TA) systems are small genetic elements ubiquitous in prokaryotic genomes that encode toxic proteins targeting various vital cellular functions. Typically, toxin activity is controlled by adjacently encoded protein or RNA antitoxins and unleashed as a consequence of genetic fluctuations or stressful conditions. Whereas some TA systems interfere with replication or cell wall synthesis, most of them influence transcriptional and post-transcriptional gene regulation. Antitoxin proteins often act as DNA binding transcriptional regulators and many TA toxins exhibit endoribonuclease activity to selectively degrade different RNA species and thus alter gene expression patterns. Some TA RNases cleave tRNA, tmRNAs or rRNAs, whereas most commonly mRNAs either in association with the ribosome or as free transcripts, are targeted. Examples are provided on how TA toxins differentially shape gene expression in bacterial pathogens by creating specialized ribosomes or by altering the transcriptome and how this may be tied in the control of pathogenicity factors.